Galactose in human metabolism, glycosylation and congenital metabolic diseases: Time for a closer look - Conte, Federica; van Buuringen, Nicole; Voermans, Nicol C.; Lefeber, Dirk J. (Biochimica et biophysica acta. General subjects, 2021)
Galactose is an essential carbohydrate for cellular metabolism, as it contributes to energy production and storage in several human tissues while also being a precursor for glycosylation. Galactosylated glycoconjugates, such as glycoproteins, keratan sulfate-containing proteoglycans and glycolipids, exert a plethora of biological functions, including structural support, cellular adhesion, intracellular signaling and many more. The biological relevance of galactose is further entailed by the number of pathogenic conditions consequent to defects in galactosylation and galactose homeostasis. The growing number of rare congenital disorders involving galactose along with its recent therapeutical applications are drawing increasing attention to galactose metabolism. In this review, we aim to draw a comprehensive overview of the biological functions of galactose in human cells, including its metabolism and its role in glycosylation, and to provide a systematic description of all known congenital metabolic disorders resulting from alterations of its homeostasis. •Galactose is an important monosaccharide for energy production and glycosylation.•Galactose-containing glycoconjugates fulfill a plethora of biological functions.•A growing number of rare congenital disorders have been linked to galactose homeostasis.•Galactosemia, six CDG and five LSDs have been linked to altered galactose metabolism.•Therapeutical applications of galactose open new horizons for disease management.